Lyotropic meso-phase behavior of supra-molecular nanotubes with helical charge distribution. Issue 19 (25th April 2017) - Wei, Shenghui; Huang, Weiheng; Su, Fengmei; Tang, Xiaoliang; Huang, Ningdong; Li, Liangbin
Abstract : We report diverse meso-phase arrangements of supra-molecular nanotubes; their transition pathway and equilibrium structure are controlled by the helical structure. Abstract : We report diverse meso-phase arrangements of supra-molecular nanotubes assembled by ionic benzene-1, 3, 5-tricarboxamide (BTA) molecules in water; their transition pathway and equilibrium structure are controlled by the helical structure. Besides, the different sensitivity to the condition of initial solutions is revealed for the final rectangular phase and the intermediate phase.